Ovary data from the Visual Sweden project DROID - Lindman, Karin; Rose, Jerónimo F.; Lindvall, Martin; Stadler, Caroline Bivik (AIDA Data Hub, 2019)
This dataset consists of 174 WSI ovary whole slide images (WSI): 158 malignant and 16 benign. Eight of the most common, histological definable tumour types were annotated: high grade serous carcinoma (HGSC), low grade serous carcinoma (LGSC), clear cell carcinoma (CC), endometrioid adenocarcinoma (EN), metastastic serous carcinoma (MS), metastatic other (MO), serous borderline tumor (SB) and mucinous borderline tumor (MB). Also normal ovarian tissue were annotated. 2402 separate annotations were made. For the benign structures only the epithelial structures, stroma and support tissue were annotated.
Keywords: Pathology; Ovary; Cancer; Whole slide imaging; Annotated; Cancer and Oncology; Cancer och onkologi; Medical and Health Sciences; Medicin och hälsovetenskap